Robinia pseudoacacia, silvicultural alternative for alto valle de Río Negro(Argentina): botanical and ecological aspects (Semiárida, 2023)
In Argentina, the cultivation of Robinia pseudoacacia is uncommon, and there are few studies on its behavior in forest plantations. Forestry research in the Alto Valle has been mainly oriented to the commercial cultivation of “poplars” and“ willows” (Salicaceae) and there are not any records on the cultivation of R. pseudoacacia. Due to the lack of information on the cultivation of this species in the region, this review aims to integrate different botanical and ecological aspects of R. pseudoacacia to evaluate its feasibility as a silvicultural alternative in the Alto Valle de Río Negro. A bibliographical review of botanical and ecological aspects of the species was carried out, as well as local field studies.  Information on the nomenclature, taxonomy, distribution, habitat, and ecology of the species is included. Robinia pseudoacacia presents plasticity and is adapted to the agro-ecological conditions of the region, so its cultivation is feasible. We expect to describe, in future contributions, aspects of the forestry-productive type that complement this review.
Keywords: afforestation; implanted forests; Patagonia; woods